(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Due to characteristics like as decentralization, openness, and immutability, the blockchain, the underlying data structure of the Bitcoin system, has gotten a lot of attention since its creation. These characteristics make blockchains ideal for applications that need disintermediation through trustless exchange, reliable and incorruptible transaction records, and operational models other than money. Blockchain and its smart contract capabilities, in particular, have the potential to address healthcare interoperability issues like enabling effective interactions between users and medical applications, securely delivering patient data to a variety of organizations and devices, and increasing the overall efficiency of medical practice workflow. Despite the growing interest in blockchain for healthcare interoperability, limited information on the specific architectural styles and patterns for utilizing blockchain in healthcare applications is accessible. This paper fills a gap in the market by demonstrating (1) the features and implementation challenges of healthcare interoperability, (2) an end-to-end case study of a blockchain-based healthcare app we’re working on, and (3) how foundational software patterns can help address common interoperability challenges faced by blockchain-based healthcare apps.